2015
DOI: 10.1053/j.ajkd.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Markers as Predictors of ESRD and Mortality in Southwestern American Indians With Type 2 Diabetes

Abstract: Background A growing number of serum filtration markers are associated with mortality and end-stage renal disease (ESRD) in adults. Whether β-trace protein (BTP) and β2-microglobulin (B2M) are associated with these outcomes in adults with type 2 diabetes is not known. Study Design Longitudinal cohort study. Setting & Participants 250 Pima Indians with type 2 diabetes (69% women; mean age, 42 years; mean diabetes duration, 11 years). Predictors Serum BTP, B2M, and glomerular filtration rate measured by io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…7 , 9 Similarly, in hemodialysis patients higher BTP was reported to be associated with increased mortality risk over a median follow-up of 3.3 years. 8 Three prior studies measured both BTP and B2M in addition to the established filtration markers creatinine and cystatin C, allowing for comparisons of ESRD, 5,17 mortality, 5,6,17 or cardiovascular risk 5 across all markers, as well as for comparisons to mGFR in Southwestern American Indians with type 2 diabetes. 17 Two prior studies reported on ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 , 9 Similarly, in hemodialysis patients higher BTP was reported to be associated with increased mortality risk over a median follow-up of 3.3 years. 8 Three prior studies measured both BTP and B2M in addition to the established filtration markers creatinine and cystatin C, allowing for comparisons of ESRD, 5,17 mortality, 5,6,17 or cardiovascular risk 5 across all markers, as well as for comparisons to mGFR in Southwestern American Indians with type 2 diabetes. 17 Two prior studies reported on ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…8 Three prior studies measured both BTP and B2M in addition to the established filtration markers creatinine and cystatin C, allowing for comparisons of ESRD, 5,17 mortality, 5,6,17 or cardiovascular risk 5 across all markers, as well as for comparisons to mGFR in Southwestern American Indians with type 2 diabetes. 17 Two prior studies reported on ESRD. In the Atherosclerosis Risk in Communities (ARIC) Study higher BTP and B2M levels were associated with increased ESRD risk and associations were both stronger than observed with eGFRcr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference may be explained by the limited accuracy of urinary markers because of several potential influences on marker levels, such as metal irons, urine pH, and complications (6,(34)(35)(36). Moreover, recent studies have shown that addition of these markers to known promoters of progression does not significantly improve prediction of the risk of ESRD in patients with relatively early DN (3,37), although both NAG and b2-MG are thought of as early markers of interstitial injury in DN (6). Almost 90% of our subjects had overt proteinuria and a reduced eGFR at baseline, and the influence of these interstitial markers on the primary end point was markedly reduced after adjustment for baseline UP and eGFR.…”
Section: Discussionmentioning
confidence: 99%